Trace analysis method for the determination of organophosphate esters based on solid-phase extraction-UPLC-MS/MS and its application to blood - Luyao Hang; Lihong Duan; Lixin Yang; Hongmei Shi (Talanta Open)
Measurement of organophosphate esters (OPEs) concentrations in human body fluids is important for understanding the level of exposure to OPEs in humans and for assessing human health risks. Currently. There are more analytical tests on the metabolite levels of OPEs in urine as biomarkers of human OPEs exposure, while there are fewer studies on the analysis of OPEs in human blood. In this study, an ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for the determination of 19 OPEs in human blood was developed based on the optimization of the pretreatment process and chromatographic separation. The serum samples were cleaned-up by an HMR extraction column, and the separation of the targets was performed on an Acquity BEHC18 column with a gradient elution using methanol and 5 mmol/L aqueous ammonium acetate as the mobile phases, and finally, the determination was carried out. Under the optimized detection conditions, the recoveries of the 19 OPEs ranged from 81.4 % to 117.8 % with the RSDs <20 %, and the limits of detection (LODs) were in the range of 0.024∼0.058 ng/mL. The method is simple in sample pretreatment, sensitive, and suitable for the determination of OPEs in human serum samples. The results of the analysis of human serum samples showed that the exposure of OPEs in human body is relatively common and should be widely concerned.